Pengaruh Nilai Nilai Agama Islam Dalam Membentuk Strategi Komunikasi Organisasi Keagamaan - Cinta Aulia Putri; Virginia Berlianie; Ismail Mubarok (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explores the impact of Islamic values in shaping communication strategies in religious organizations. Through a qualitative approach, this study analyzes how Islamic principles, such as justice, loyalty, and mutual understanding, are reflected in organizational communication processes. Research findings show that Islamic values play a crucial role in shaping messages, communication structures, and interactions among organizational members. Communication strategies based on Islamic values tend to strengthen organizational identity, create internal harmony, and gain external support. The implications of this study highlight the importance of understanding the context of religious values in designing effective communication strategies for religious organizations.